Critical policy Analysis - O'Sullivan, Dominic; Came, Heather (Encyclopedia of Health Research in the Social Sciences, 2023)
Critical policy analysis (CPA) is a technique concerned with how the location of power within the policy system influences social outcomes. CPA shows how and why it is unreasonable to assume that policy making is a politically neutral, objective, and simple technical process. This entry illustrates critical policy analysis through the example of colonial health policy in New Zealand. Institutional racism is often normalised within colonial settings and CPA can respond with a range of tools to privilege Indigenous values and contexts in policy development and implementation. Critical Tiriti Analysis is an emerging CPA method of policy analysis. It emphasises making policy transparently, with substantive Māori (Indigenous peoples of New Zealand) leadership. It is becoming increasingly influential among policy makers in New Zealand with the potential to counter racism as a modifiable determinant of health, for example.
Keywords: Public Policy; Te Tiriti o Waitangi

Whānau Ora: An Indigenous policy success story - Boulton, Amohia; Smith, Verna; Moore, Charlotte; Cumming, Jacqueline (Successful Public Policy: Lessons from Australia and New Zealand, 2019)
Keywords: Health; Māori; Māori Health; Public Policy; Whanau Ora